The Concept of "Humanity" in the Perspective of Maqāṣid Al-Sharī’ah - Moh. Husnul Affan; Asep Awaludin (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2023)
The application of sharia in Islam is a matter that must be done, in the form of worship, mua'amalah and law. However, in legal practice, often the application of the Shari'ah encounters many obstacles in the form of protests or rejections from many parties. This is triggered by the conception of Human Rights (HAM) which has been raised by the West in the 19th century. Thus, it is widely stated that shari'ah in Islam, especially in the application of law (hudūd) is widely seen as treatment that is not in accordance with human rights. However, it turns out that the conception of human rights and humanity implied in it still has various epistemological and theological problems. Human rights that have been discoursed by the West are completely loaded with the paradigm of Humanism-Secular which is very contradictory in Islam. For this reason, Muslims design a separate conception of human rights that is in accordance with the Islamic worldview. So, in this article, the author will discuss the suitability of the purpose of implementing sharia or maqāṣid al-sharī'ah with humanity based on an Islamic view. The writing of this article uses qualitative research methods with a library research model. The writing of this article uses qualitative research methods with a library research model.